Smart Industry - Better Management. - Bondarouk, Tanya. (Advanced Series in Management Series, 2022)
The ebook edition of this title is Open Access and freely available to read online. Smart Industry, Better Management explores concepts in future-proofing industrial and product systems, use of cyber physical systems, digitization, interconnectivity, and new manufacturing and product technologies.